Relatório de estágio curricular supervisionado em medicina veterinária – área de inspeção de produtos de origem animal - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work describes the activities carried out during the Supervised Curricular Internship in Veterinary Medicine (ECSMV). This was carried out in the Inspection of Products of Animal Origin area, with the Ministry of Agriculture, Livestock and Supply (MAPA). The Federal Inspection Service, under registration number SIF 2007, is responsible for supervising the activities dedicated to the slaughter of cattle at Frigorífico Marfrig Global FoodsS / A, located in the city of Alegrete in the state of Rio Grande do Sul. The internship was carried out under guidance Profa. Dr. Claudete Izabel Funguetto and supervision of Veterinary Doctor Clóvis Roberto Arnoud Grande, from August 21 to November 13, 2018, totaling 450 hours. Throughout the supervised internship, routine procedures were followed in the Marfrig refrigerator, from disembarking and receiving the animals on site, washing and disinfecting trucks, ante-mortem inspection, post-mortem inspection through inspection lines, Department of Final Inspection (DIF) , kids sector, dowries, triparia, dessosa and packaging. The main activities carried out were carrying out ante-mortem and post-mortem examinations of animals. The development of the curricular internship at the Ministry of Agriculture, Livestock and Supply, made it possible to know the routine experienced by the Veterinary Doctor who works in Food Inspection and to understand the importance of the one that ensures that the Products of Animal Origin arrive harmless to the population's consumption.
Supervised internship report on veterinary medicine - animal products inspection area
Keywords: Medicina veterinária; Inspeção de produtos de origem animal; Inspeção sanitária; Inspeção de carne e produtos derivados; Inspeção de alimentos; Veterinary Medicine; Inspection of products of animal origin; Sanitary inspection; Inspection of meat and meat products; Food inspection; CNPQ::CIENCIAS AGRARIAS